Utilization of Learning Modules to Overcome Learning Loss in Elementary Schools - Muhisom Muhisom; Erni Erni; Dayu Rika Perdana; Amrina Izzatika (Budapest International Research and Critics University, 2023)
The purpose of this research is to see how learning modules can be well developed so that learning loss does not occur. Education in Indonesia applies K13; the orientation of the 2013 curriculum is an increase and a balance between attitude competence, skills and knowledge. In other words, the teacher is a facilitator, besides that the teacher must be able to develop the teaching materials used so that students do not feel bored and bored when learning mathematics. The ways that teachers can do to create and develop teaching materials include using an approach in the process of developing teaching materials, which are in accordance with the material to be delivered. One type of teaching material that can be developed by the teacher is a learning module. Research results show that the benefits for students in module development. One of them is to make it easier for students to understand the material, create effective learning and provide meaningful learning for students. The developed learning modules will be more useful and advance education properly to prevent learning loss from occurring.